2011
DOI: 10.1111/j.1440-1789.2010.01129.x
|View full text |Cite
|
Sign up to set email alerts
|

An autopsied case of sporadic adult-onset amyotrophic lateral sclerosis with FUS-positive basophilic inclusions

Abstract: Basophilic inclusions (BIs), which are characterized by their staining properties of being weakly argyrophilic, reactive with Nissl staining, and immunohistochemically negative for tau and transactive response (TAR) DNA-binding protein 43 (TDP-43), have been identified in patients with juvenile-onset amyotrophic lateral sclerosis (ALS) and adult-onset atypical ALS with ophthalmoplegia, autonomic dysfunction, cerebellar ataxia, or a frontal lobe syndrome. Mutations in the fused in sarcoma gene (FUS) have been r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 23 publications
(46 reference statements)
2
24
2
Order By: Relevance
“…29,33 If we take these results together, our data support the hypothesis of an active and at least partially independent bilateral cortical process of degeneration with secondary damage to the CC, particularly in its midbody, known to be significantly involved in the process of axonal degeneration in ALS 34 and substantially formed by interhemispheric fibers connecting the motor cortices, as also demonstrated by diffusion tensor tractography. 35 According to previous neuropathologic findings, 27,34,36 ALS degenerative changes in the cerebral cortex mainly involve motor areas, though recent whole-brain voxel-based morphometry analyses have largely reported GM abnormalities even in extramotor regions. 12,14,15,20,31,37 Thereby, the trends of MD and RD changes, which largely overlapped in our patients in both the genu and splenium of the CC, may represent an increase in the extracellular volume secondary to axonal loss associated with injury to the myelin sheaths, as previously reported in human and animal models of demyelination and axonal degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…29,33 If we take these results together, our data support the hypothesis of an active and at least partially independent bilateral cortical process of degeneration with secondary damage to the CC, particularly in its midbody, known to be significantly involved in the process of axonal degeneration in ALS 34 and substantially formed by interhemispheric fibers connecting the motor cortices, as also demonstrated by diffusion tensor tractography. 35 According to previous neuropathologic findings, 27,34,36 ALS degenerative changes in the cerebral cortex mainly involve motor areas, though recent whole-brain voxel-based morphometry analyses have largely reported GM abnormalities even in extramotor regions. 12,14,15,20,31,37 Thereby, the trends of MD and RD changes, which largely overlapped in our patients in both the genu and splenium of the CC, may represent an increase in the extracellular volume secondary to axonal loss associated with injury to the myelin sheaths, as previously reported in human and animal models of demyelination and axonal degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Another example of pathological inclusions found in ALS and FTD are basophilic inclusions. Basophilic inclusions are negative for TDP-43, but are positive for FUS and a number of other RNA binding proteins (3-5, 9, 16-19). TDP-43 and FUS are proteins involved in a range of RNA biogenesis processes, including the transport of RNA transcripts into cytoplasmic stress granules (20, 21).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a single case has been described in the literature with adult-onset FUS mutation-negative SALS with FUS-immunoreactive basophilic inclusions (Matsuoka et al 2011). In this case, the inclusions were immunopositive for p62, LC3, and FUS, but immunonegative for tau, TDP-43, and neurofilament (Matsuoka et al 2011).…”
Section: Family 6885mentioning
confidence: 89%
“…Histopathological analyses in these studies have shown these inclusions to be immunoreactive for FUS, p62, and ubiquitin but negative for TDP-43, hyperphosphorylated tau, α-synuclein, α-1-internexin, and neurofilament (Baumer et al 2010;Huang et al 2010;Suzuki et al 2010). Recently, a single case has been described in the literature with adult-onset FUS mutation-negative SALS with FUS-immunoreactive basophilic inclusions (Matsuoka et al 2011). In this case, the inclusions were immunopositive for p62, LC3, and FUS, but immunonegative for tau, TDP-43, and neurofilament (Matsuoka et al 2011).…”
Section: Family 6885mentioning
confidence: 92%